Built of Cermet Layer Using Thermal Plasma Spraying (APS) - Madlul, Safaa F; A, Sabah M; Abdullah, Seham S (Al-Nahrain Journal of Science, 2011)
The technology of thermal plasma spray take an advanced position among different coating technologies, because of it`s allowing to use a wide range of engineering materials depending on it`s melting point, to get a super mechanical, electrical, and thermal properties in comparing with other thermal spray methods. So it is improves the properties of metals, ceramics, and plastics parts which are used in industry at all.